Increasing access to essential medicines through partnership: experience in developing and delivering chlorhexidine gel for newborn cord care - Andrew Clarke; Rachel Gibson; Elena DeAngelis; Karrar Karrar; Pauline Williams (BMJ Publishing Group, 2022)
Sustainable access to essential medicines in low-income and middle-income countries requires innovative cross-sectoral collaboration throughout the lifecycle of a medicine. Partnerships are essential to address the systemic challenges of global health and health inequity. Pharmaceutical companies, funders, governments, international non-governmental organisations (I-NGOs) and other key stakeholders can leverage, through effective partnership working, their unique expertise to help drive innovation and share learnings and risks. Here, we reflect on one approach taken in the development and supply of chlorhexidine digluconate 7.1% w/w gel (equivalent to 4% w/w chlorhexidine) for neonatal cord care. We describe and analyse the steps taken by GSK to increase access to chlorhexidine gel, including partnering with the I-NGO Save the Children in Western Kenya. Learning points gained along the journey are shared, together with subsequent steps taken to increase access, with the aim of making recommendations that may be applicable to similar enterprises in the future.